Sleep problems and childhood adiposity: a cross-sectional study among third-grade students in Shanghai, China - Shuman Li; Zhe Zhang; Yani Zhai; Liting Chu; Dongling Yang; Chunyan Luo; Lijing Sun (Frontiers in Public Health)
ObjectiveTo investigate the association between sleep problems and overweight or obesity among third-grade primary school students in Shanghai, China.MethodsA total of 3,640 students aged 8–10 years were recruited in 2023 using a random cluster sampling method. Sleep problems were assessed using the Children’s Sleep Habits Questionnaire (CSHQ). Anthropometric measurements, including weight, height, and waist circumference, were collected to calculate body mass index (BMI) and waist-to-height ratio (WHtR).ResultsThe prevalence of overweight or obesity was 31.7%. The average sleep duration was 9.2 ± 0.6 h, and the mean total CSHQ score was 47.8 ± 7.5. Weekend sleep duration was negatively associated with BMI (β = −0.188, p < 0.01). Higher Sleep Disordered Breathing scores were positively associated with BMI (β = 0.246, p < 0.01) and WHtR (β = 0.005, p < 0.01), while higher Daytime Sleepiness scores were negatively associated with both BMI (β = −0.056, p < 0.01) and WHtR (β = −0.001, p < 0.05). Higher Sleep Duration scores were negatively associated with BMI (β = −0.067, p < 0.05). In logistic regression models, Sleep Disordered Breathing was significantly associated with higher odds of both overweight/obesity (OR = 1.39, 95% CI: 1.13–1.70), and central obesity (OR = 1.36, 95% CI: 1.11–1.68). These associations were more evident among boys.ConclusionDifferent dimensions of sleep problems showed varying associations with overweight/obesity and central obesity in children, with stronger associations observed among boys.